Overview of drugs used for the treatment of hypertension for elderly patients in Sanglah General Hospital, Denpasar, Bali - Archana Laxmi Pathmanathan; I Nyoman Gede Wardana; I Gusti Ayu Widianti (Intisari Sains Medis, 2019)
Background: Hypertension is one of the most common diseases among elderly patients and it is also known as a silent killer. It could be due to excessive stress which causes the blood pressure to rise. The symptoms could appear, and people could go on for years without having any awareness of their disease. Aim: This research was conducted to determine the prevalence of hypertension cases of elderly patients and the drugs used as a treatment for hypertension in Sanglah Hospital, Denpasar, Bali. The research was carried on in the Sanglah Hospital, Denpasar, Bali as of January until June 2017. Method: In this study, a descriptive cross sectional study method was being used. Result: As the age increases, the number of individuals with hypertension increases. In gender, we could see that the female has a higher prevalence compared to male. In Sanglah, we found that the mostly given drugs are amlodipine and captopril for elderly people as this drug works effectively for the patients. Other drugs such as valsartan, furosemide, and bisoprolol are also offered to patients with hypertension depending on their associated diseases.